Internally Displaced and Immobile People in Ukraine Between 2014 and 2022: Older Age and Disabilities as Factors of Vulnerability - International Organization for Migration (United Nations, 2023)
Authored by Irina Kuznetsova and Oksana Mikheieva, this Migration Research Series paper explores the impacts of the ongoing crisis in Ukraine on the individuals that were displaced before 2022. The authors argue that the pre-existing vulnerabilities of those stranded in occupied areas since February 2022 have been exacerbated, particularly at the intersections of displacement and immobility, and disability, older ag, and housing.